Stress analysis of the elbow joint under constraint and semi-constraint type implant made of CoCrMo alloys - Khairul Shahri Abdul Rokib, 1987-; Mohammed Rafiq Abdul Kadir; Fakulti Kejuruteraan Mekanikal (2010)
Project Paper (Sarjana Muda Kejuruteran (Mekanikal - Bahan)) - Universiti Teknologi Malaysia, 2010